Penggunaan Media Ular Tangga terhadap Hasil Belajar Metematika - Imam Baiquni (JKPM (Jurnal Kajian Pendidikan Matematika), 2016)
The aim of the experiment research was to know the effect of the snake ladder media on math achievement. The design that was used in this research was true experimental design in the form of post-test only control design. This research was conducted in the third class of Elementary School (SD) Islam Tariq Bin Ziyad Bekasi, academic year 2014-2015 that consist of three parallel classes. Sample was taken randomly, and then it’s divided into two groups, experiment group (class III.C) and control group (class III.B). After the two groups were treated differently, both groups were each given a post-test by an instrument that consists of 25 items in multiple choice forms with 4 alternative answers. As these instruments have been tested beforehand and validated empirically. Analysis of data used t-test, by testing normality and homogeneity first. The result of the research showed that there is an effect of using flash card math on mathematics achievement, especially on a simple fraction in the third class of Elementary School (SD) Islam Tariq Bin Ziyad Bekasi.